Effect of nickel supplementation on the antioxidant and immune status of growing lambs - Chandra, Gulab (The Indian Journal of Animal Sciences, 2026)
The present investigation aimed to investigate the impact of nickel (Ni) supplementation on the antioxidant and immune status of growing Muzaffarnagari lambs. For this study, 18 healthy Muzaffarnagari lambs were sorted out from the herd according to weight and age (30.45±3.67 kg) and age (10.33±0.67 months) and randomly divided into 3 groups, 5 in each. The ingredients composition of the basal diet composition was similar for all three groups except nickel supplemented at dose 0.0 (control), 1.5 (Ni1.5), and 3.0 (Ni3.0) mg/kg DM in the respective group for 90 days of study. The jugular blood was drawn on days 0, 15, 30, 45, 60, 75, and 90 of the study in the morning before feeding and watering. The superoxide dismutase (SOD), total antioxidant activity (TAA), and thiobarbituric acid reactive substance (TBARS) did not vary statistically among the group control, Ni1.5, and Ni3.0. Whereas, catalase activity was statistically (P